Квантовая биэкситонная жидкость в кристаллах моноклинного ZnP₂ - Горбань, И.С.; Ещенко, О.А.; Дмитрук, И.М.; Белый, Н.М. (Физика низких температур, 2001)
Предложен фонон-ротонный закон дисперсии элементарных возбуждений квантовой биэкситонной жидкости в полупроводниках. Исходя из предложенного закона дисперсии рассчитан спектр фотолюминесценции (ФЛ) жидкости и исследовано его поведение при изменении температуры и плотности биэкситонной жидкости. Путем аппроксимации экспеpиментального спектра фотолюмине-сценции биэкситонной жидкости полупроводниковых кристаллов β-ZnP₂ расчетным спектром определены значения параметров кривой дисперсии элементарных возбуждений квантовой биэкситонной жидкости. Экспериментальные исследования зависимости спектра ФЛ биэкситонной жидкости в β-ZnP₂ от температуры и интенсивности лазерного возбуждения подтверждают исходную теоpетическую модель. Измерены зависимости температуры кристаллов от интенсивности возбуждения. Для нескольких образцов получены аномальные зависимости: температура кристалла уменьшалась при увеличении интенсивности возбуждения. Этот эффект, вероятно, является следствием гигантской теплопроводности сверхтекучей биэкситонной жидкости в кристаллах β-ZnP₂. A phonon–roton dispersion relation is proposed for the elementary excitations of a quantum biexcitonic liquid in semiconductors. A phonon–roton dispersion relation is proposed for the elementary excitations of a quantum biexcitonic liquid in semiconductors. The proposed dispersion relation is used as a starting point for a calculation of the photoluminescence spectrum of the liquid and an analysis of its behavior under variation of temperature and density of the biexcitonic liquid. The parameters of the dispersion curve of elementary excitations of the quantum biexcitonic liquid are evaluated by fitting the calculated photoluminescence spectrum to the experimental spectrum of the biexcitonic liquid of semiconducting β-ZnP₂ crystals. Experimental studies of how the photoluminescence spectrum of a biexcitonic liquid in β-ZnP₂ depends on the temperature and the intensity of the laser excitation confirm the initial theoretical model. The dependence of the temperature of the crystals on the excitation intensity is measured, and for some of the samples an anomalous dependence is found: the temperature of the crystal decreases as the excitation intensity increases. This effect is probably a consequence of the giant thermal conductivity of the superfluid biexcitonic liquid in β-ZnP₂ crystals.